Raymond Williams on culture & society : essential writings - Williams, Raymond; McGuigan, Jim (Los Angeles : SAGE, 2014)
The work of Raymond Williams remains hugely influential, not just in the humanities but across the social sciences too. This collection introduces a new generation of students to a major figure in sociology, media studies and cultural studies.
Includes index.
Specialized.
Description based on print version record.
Keywords: Culture -- Philosophy; Sociology -- Philosophy; Philosophy, Marxist